2021
DOI: 10.1111/acem.14215
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing prescribed light exercise to standard management for emergency department patients with acute mild traumatic brain injury

Abstract: Background: There is a paucity of effective management strategies to prevent prolonged symptoms following mild traumatic brain injury (mTBI), and emerging evidence suggesting possible benefits of exercise. The objective of this trial was to determine whether adult patients presenting to the emergency department (ED) with a diagnosis of acute mTBI prescribed light exercise were less likely to develop persistent postconcussion symptoms (PCS).Methods: This was a randomized controlled trial conducted in three Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…With participants spending the majority of their time in light PA, it may be concluded that light intensity may not be sufficient enough to induce a therapeutic response after concussion. This intensity insufficiency was also noted by Varner et al 27 who found no significant changes in symptoms when implementing a 30minute light PA regiment after mTBI. Conversely, other previous research has utilized a more structured treadmill-based approach in which participants determine their intensity based on symptom exacerbation.…”
Section: Discussionsupporting
confidence: 76%
“…With participants spending the majority of their time in light PA, it may be concluded that light intensity may not be sufficient enough to induce a therapeutic response after concussion. This intensity insufficiency was also noted by Varner et al 27 who found no significant changes in symptoms when implementing a 30minute light PA regiment after mTBI. Conversely, other previous research has utilized a more structured treadmill-based approach in which participants determine their intensity based on symptom exacerbation.…”
Section: Discussionsupporting
confidence: 76%
“…[25][26][27] It is reasonable to recommend for 24 to 48 hours of cognitive and physical rest, followed by a gradual return to normal activities as tolerated. 26,28 Some recent studies suggest that low-intensity physical activity during the initial days of a concussion may be safe and even assist in recovery from prolonged symptoms than activity avoidance 25,[29][30][31] ; however, the current understanding of optimal intensity, duration, and frequency is limited.…”
Section: Discussionmentioning
confidence: 99%
“…17 At the time of the study, most guidelines recommended 24 to 48 hours of cognitive and physical rest 26 ; however, recent research has suggested that early light exercise may not be harmful. 31 Finally, although it is possible that physicians may have provided more treatment advice than their standard care, at the time of the study, they were not aware of the specific research question.…”
Section: Discussionmentioning
confidence: 99%
“…However, further work is required to understand if a low-level activity prescription (i.e., a step count strategy) results in faster recovery compared to a higher intensity exercise recommendation (i.e., exercise prescription based on HR). One study compared adults who were randomized to a prescription of 30 min of daily light exercise vs. gradual return to exercise after symptom resolution and found no differences in recovery outcomes [ 28 ]. Thus, low level intensity/volume exercise may also not provide the necessary dose to induce a meaningful clinical benefit especially in a population of highly active adolescents.…”
Section: Discussionmentioning
confidence: 99%